Antibody-mediated rejection after liver transplantation-relevance of C1q and C3d-binding antibodies - Kovandova, Barbora; Slavcev, Antonij; Sekerkova, Zuzana; Honsova, Eva; Trunecka, Pavel (HLA, 2018)
The aim of our study was to evaluate the relevance of complement-binding donor-specific antibodies (DSA) for prediction of antibody-mediated rejection (AMR) after liver transplantation. Sera from 123 liver transplant recipients were retrospectively defined for HLA specificity and complement-fixing activity using the single antigen beads, C1q and C3d techniques. Liver-recipients' sera were tested before transplantation, 3, 6 months and 1 year after transplantation. Patients were followed up for graft survival and rejection incidence for 1 year after transplantation. All patients with pretransplant complement-binding DSA developed severe AMR after transplantation, while three recipients out of four, who produced de novo complement-fixing DSA, developed AMR. Definition of DSA with respect to complement-fixing activity may provide clinically relevant information about the risk of AMR after liver transplantation.
Keywords: Transplantation, Homologous; Histocompatibility Testing; dospělí; komplement C1q; Complement C3d; Prognosis; komplement C3d; retrospektivní studie; Humans; následné studie; lidé středního věku; dárci tkání; Middle Aged; Tissue Donors; homologní transplantace; prognóza; Follow-Up Studies; Complement C1q; mužské pohlaví; isoprotilátky; Adult; Adolescent; Graft Survival; transplantace jater; ženské pohlaví; Female; Isoantibodies; rejekce štěpu; přežívání štěpu; lidé; mladiství; dítě; Child; Graft Rejection; Aged; senioři; Male; Retrospective Studies; Liver Transplantation; testování histokompatibility